2016
DOI: 10.1038/sc.2016.86
|View full text |Cite
|
Sign up to set email alerts
|

Type, intensity and duration of daily physical activities performed by adults with spinal cord injury

Abstract: Given that some groups were more likely to engage in moderate-heavy-intensity activities, and some activities were more likely to be performed at moderate-heavy intensities, interventions that target key groups to increase certain daily activities may be one strategy to enhance overall physical activity participation among people with SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Although LTPA is an important component for improving positive psychological well-being and quality of life among a population with chronic SCI [10], performing LTPA alone may not necessarily be sufficient to provide health benefits or raise cardiometabolic fitness [11]. In addition, activities of daily living among individuals with SCI who use wheelchairs, as opposed to the able-bodied, may not be adequate for producing intensities that are health beneficial [12,13], though some studies have reported otherwise [14,15]. Therefore, in a population with SCI, the need for moderate-vigorous intensity LTPA performed over an adequate amount of time and frequency is crucial in maintaining or improving cardiometabolic fitness and muscle strength.…”
Section: Introductionmentioning
confidence: 99%
“…Although LTPA is an important component for improving positive psychological well-being and quality of life among a population with chronic SCI [10], performing LTPA alone may not necessarily be sufficient to provide health benefits or raise cardiometabolic fitness [11]. In addition, activities of daily living among individuals with SCI who use wheelchairs, as opposed to the able-bodied, may not be adequate for producing intensities that are health beneficial [12,13], though some studies have reported otherwise [14,15]. Therefore, in a population with SCI, the need for moderate-vigorous intensity LTPA performed over an adequate amount of time and frequency is crucial in maintaining or improving cardiometabolic fitness and muscle strength.…”
Section: Introductionmentioning
confidence: 99%
“…Only education had a significant interaction effect on PA over time, with people with higher education increasing their PA behaviour more than people with lower education. Previous research also found that people with higher education were more active, but to the best of our knowledge, the association between education and longitudinal change of PA behaviour was not studied before 24 57…”
Section: Discussionmentioning
confidence: 69%
“…Furthermore, strategies to increase physical activity may be more successful if they are integrated into adapted activities and/or those that directly align with an individual's goals (i.e., gardening, walking a dog, cycling, resistance training, yoga etc.) 31 .…”
Section: Discussionmentioning
confidence: 99%